Environment-Mediated Accumulation of Diacyl Lipoproteins over Their Triacyl Counterparts in Staphylococcus aureus - Kurokawa, Kenji (American Society for Microbiology, 2012)
Bacterial lipoproteins are believed to exist in only one specific lipid-modified structure, such as the diacyl form or the triacyl form, in each bacterium. In the case of Staphylococcus aureus, recent extensive matrix-assisted laser desorption ionization–time of flight (MALDI-TOF) mass spectrometry analysis revealed that S. aureus lipoproteins exist in the α-aminoacylated triacyl form. Here, we discovered conditions that induce the accumulation of diacyl lipoproteins that lack α-aminoacylation in S. aureus. The accumulation of diacyl lipoproteins required a combination of conditions, including acidic pH and a post-logarithmic-growth phase. High temperatures and high salt concentrations additively accelerated the accumulation of the diacyl lipoprotein form. Following a post-logarithmic-growth phase where S. aureus MW2 cells were grown at pH 6, SitC lipoprotein was found almost exclusively in its diacyl structure rather than in its triacyl structure. This is the first report showing that the environment mediates lipid-modified structural alterations of bacterial lipoproteins.